2013
DOI: 10.1186/1471-2458-13-1004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of barriers to the prevention and treatment of heat-related illness in Latino farmworkers using activity-oriented, participatory rural appraisal focus group methods

Abstract: BackgroundHeat-related illness (HRI) is an important cause of non-fatal illness and death in farmworkers. We sought to identify potential barriers to HRI prevention and treatment in Latino farmworkers.MethodsWe conducted three semi-structured focus group discussions with 35 Latino farmworkers in the Central Washington, USA area using participatory rural appraisal techniques. Interviews were audio taped and transcribed in Spanish. Three researchers reviewed and coded transcripts and field notes, and investigato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 30 publications
(36 reference statements)
3
61
1
1
Order By: Relevance
“…Under Cal-OSHA requirements, farmers are required to provide heat illness prevention training for workers and offer regular breaks to cool off and rehydrate (Cal-OSHA Heat Illness Regulation 3395). Despite research that suggests workers do not remember the information provided in the trainings and do not take recommended breaks,4 43 our estimates of heat strain indicate that workers in our sample do not experience high levels of heat strain. This may be related to the different farm tasks performed, suggesting that not all farm work is strenuous.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Under Cal-OSHA requirements, farmers are required to provide heat illness prevention training for workers and offer regular breaks to cool off and rehydrate (Cal-OSHA Heat Illness Regulation 3395). Despite research that suggests workers do not remember the information provided in the trainings and do not take recommended breaks,4 43 our estimates of heat strain indicate that workers in our sample do not experience high levels of heat strain. This may be related to the different farm tasks performed, suggesting that not all farm work is strenuous.…”
Section: Discussioncontrasting
confidence: 68%
“…Other estimates of fluid intake among agricultural workers suggest that the amount of water workers drink is not sufficient to replace fluids and electrolytes lost during the work shift,6 as many do not believe they are at risk for injury and do not adequately rehydrate 5. In addition, agricultural workers often distrust water supplied by employers, and do not bring enough of their own water to adequately hydrate during the day 43. However, the lack of association of volume depletion to AKI was surprising, given the above findings.…”
Section: Discussionmentioning
confidence: 99%
“…Those who are paid by the piece may be more reluctant to take recommended breaks to rest in the shade or drink water because stopping work cuts into time that could be spent picking and may result in lower wages. 28 Therefore, those paid by the piece may inadvertently expose themselves to greater levels of occupational hazards, including heat illness and dehydration, 29 which may prove damaging to the kidneys. Fortunately, the method of paying agricultural workers is a modifiable risk factor and could be an approach to reducing incident AKI over a work-shift.…”
Section: Discussionmentioning
confidence: 99%
“…They also identified several factors that potentially reduce heat-related illness, including increasing breaks in the shade, increasing access to medical attention, reducing soda intake or increasing access to regular breaks. Lam et al 16 interviewed 35 Hispanic farmworkers in Washington and identified several barriers to prevent them from heat-related illness. To the best of our knowledge, no studies examined heat effects among migrant and seasonal farmworkers using clinical data.…”
Section: Introductionmentioning
confidence: 99%